Effects of canagliflozin versus finerenone on cardiorenal outcomes: exploratory post hoc analyses from FIDELIO-DKD compared to reported CREDENCE results. Issue 7 (25th November 2021) - Agarwal, Rajiv; Anker, Stefan D; Filippatos, Gerasimos; Pitt, Bertram; Rossing, Peter; Ruilope, Luis M; Boletis, John; Toto, Robert; Umpierrez, Guillermo E; Wanner, Christoph; Wada, Takashi; Scott, Charlie; et al.
ABSTRACT: Background: The nonsteroidal mineralocorticoid receptor antagonist finerenone and the sodium–glucose cotransporter-2 inhibitor (SGLT-2i) canagliflozin reduce cardiorenal risk in albuminuric patients with chronic kidney disease (CKD) and type 2 diabetes (T2D). At first glance, the results of Finerenone in Reducing Kidney Failure and Disease Progression in Diabetic Kidney Disease (FIDELIO-DKD) (ClinicalTrials.gov, NCT02540993) and Canagliflozin and Renal Events in Diabetes with Established Nephropathy Clinical Evaluation (CREDENCE) appear disparate. In FIDELIO-DKD, the primary endpoint had an 18% [95% confidence interval (CI) 7–27] relative risk reduction; in CREDENCE, the primary endpoint had a 30% (95% CI 18–41) relative risk reduction. Unlike CREDENCE, the FIDELIO-DKD trial included patients with high albuminuria but excluded patients with symptomatic heart failure with reduced ejection fraction. The primary endpoint in the FIDELIO-DKD trial was kidney specific and included a sustained decline in the estimated glomerular filtration rate (eGFR) of ≥40% from baseline. In contrast, the primary endpoint in the CREDENCE trial included a sustained decline in eGFR of ≥57% from baseline and cardiovascular (CV) death. This post hoc exploratory analysis investigated how differences in trial design—inclusion/exclusion criteria and definition of primary outcomes—influenced observed treatment effects. Methods: Patients from FIDELIO-DKD who met the CKD inclusion criteria of the CREDENCE study (urine albumin: creatinine ratio >300–5000 mg/g and an eGFR of 30–<90 mL/min/1.73 m 2 at screening) were included in this analysis. The primary endpoint was a cardiorenal composite (CV death, kidney failure, eGFR decrease of ≥57% sustained for ≥4 weeks or renal death). Patients with symptomatic heart failure with reduced ejection fraction were excluded from FIDELIO-DKD. Therefore, in a sensitivity analysis, we further adjusted for the baseline prevalence of heart failure. Results: Of 4619/5674 (81.4%) patients who met the subgroup inclusion criteria, 49.6% were treated with finerenone and 50.4% received placebo. The rate of the cardiorenal composite endpoint was 43.9/1000 patient-years with finerenone compared with 59.5/1000 patient-years with placebo. The relative risk was significantly reduced by 26% with finerenone versus placebo [hazard ratio (HR) 0.74 (95% CI 0.63–0.87)]. In CREDENCE, the rate of the cardiorenal composite endpoint was 43.2/1000 patient-years with canagliflozin compared with 61.2/1000 patient-years with placebo; a 30% risk reduction was observed with canagliflozin [HR 0.70 (95% CI 0.59–0.82)]. Conclusions: This analysis highlights the pitfalls of direct comparisons between trials. When key differences in trial design are considered, FIDELIO-DKD and CREDENCE demonstrate cardiorenal benefits of a similar magnitude. Graphical Abstract: